2022
DOI: 10.3390/ijerph191811652
|View full text |Cite
|
Sign up to set email alerts
|

Back to School: Italian Teachers’ Perceptions of the Impact of COVID-19 on Personal and Social Well-Being and Teaching Methods

Abstract: During the COVID-19 pandemic, continuous closing and reopening of schools may have had an impact on teachers’ perception of the risk of contracting SARS-CoV-2 and of the effectiveness of health measures introduced to limit the spread of the virus, with consequences on teaching methods and relational bonds within schools. By means of an online survey, we measured: teachers’ stress, job-satisfaction, self-efficacy and emotions at work, risk-perception of contracting SARS-CoV-2, perception of effectiveness of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…A mixed-methods study conducted by Hidalgo-Andrade et al [107] concluded that social support (family, friends, spiritual activities) was the most frequently used coping strategy during the pandemic to manage psychological distress followed by leisure activities, mental health promotion (psychological well-being), and work with study (professional growth). Another study conducted by Porru et al [108] assessed teacher's perception of risk to contract COVID and the effectiveness of health measures (EHM). The risk perceptions were used as mediating variables to examine the causal impact of teacher stress, and cognitive factors (job satisfaction, self-efficacy and emotional intensity) and their perceptions of COVID-19 on dependent variables (teaching methods and social relationships at school).…”
Section: Teacher Coping and Conflict Management During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…A mixed-methods study conducted by Hidalgo-Andrade et al [107] concluded that social support (family, friends, spiritual activities) was the most frequently used coping strategy during the pandemic to manage psychological distress followed by leisure activities, mental health promotion (psychological well-being), and work with study (professional growth). Another study conducted by Porru et al [108] assessed teacher's perception of risk to contract COVID and the effectiveness of health measures (EHM). The risk perceptions were used as mediating variables to examine the causal impact of teacher stress, and cognitive factors (job satisfaction, self-efficacy and emotional intensity) and their perceptions of COVID-19 on dependent variables (teaching methods and social relationships at school).…”
Section: Teacher Coping and Conflict Management During Covid-19mentioning
confidence: 99%
“…The study also found that cognitive factors had an indirect effect on dependent variables through risk perception of contracting COVID-19 and EHM. The study highlights the importance of stress and presence of cognitive coping strategies (self-efficacy and emotional intensity) in school teachers [108]. The emotional competence and ability to handle conflicts of primary school teachers was examined in terms of socio-demographic (sex, age, have own children) and professional (teaching experience, type of school) variables and their ability to manage students (interpret student emotions, respect for students).…”
Section: Teacher Coping and Conflict Management During Covid-19mentioning
confidence: 99%
“…Therefore, the other reason lies in the area of instructional framework applicable for emergency remote teaching. Specifically, the factor of the abrupt transition to online instructional mode appeared to be a cornerstone for the majority of educators and institutions [3,53]. This could mean that the stage of course conceptualization requires a more universal and flexible design approach that could enable educators to adjust developed syllabi in the most efficient manner in case of a social demand.…”
Section: What Educational Theories Should Underpin the Ert Instructio...mentioning
confidence: 99%
“…A socially supportive climate in the teaching profession seems to be a resource for teacher well-being, whereas conflicting peer relations among teachers seem to raise teacher burnout [40]. Further, emotional regulation and teachers' stress levels were key factors affecting relationship quality in schools [41].…”
Section: School Climatementioning
confidence: 99%